2017
DOI: 10.1210/en.2016-1687
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the Femoral Head: Lipotoxicity Exacerbation in MSC and Modifications of the Bone Marrow Fluid

Abstract: Osteonecrosis of the femoral head (ON) is a multifactorial bone disease that can evolve to a progressive destruction of the hip joint. Different pathogenic processes have been proposed, among them, an increase of bone marrow (BM) fat resulting from adipocyte accumulation. Marrow adipocytes are active BM residents that influence the microenvironment by releasing cytokines, adipokines, and free fatty acids (FA). We explored the impact of palmitate (Palm) and oleate on function and survival of BM-derived mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…However, the mechanisms behind stem cell therapy remained unclear and may be partly explained by the theory of biological characteristics [ 49 , 50 ]. Since stem cells have the capabilities of self-renew and proliferation, when injected into necrotic femoral head, they could differentiate into osteoblast, chondrocyte, and other tissues to repair dead bones [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms behind stem cell therapy remained unclear and may be partly explained by the theory of biological characteristics [ 49 , 50 ]. Since stem cells have the capabilities of self-renew and proliferation, when injected into necrotic femoral head, they could differentiate into osteoblast, chondrocyte, and other tissues to repair dead bones [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMSCs) are the common precursor cell to adipocytes and osteoblast cells. Adipocytes accumulation or lipid toxicity is frequently reported in various diseases, including postmenopausal osteoporosis, aging osteoporosis and osteonecrosis (Gillet et al, 2017). Some investigators found that bone marrow adipocytes could suppress osteoblast differentiation through secreting factors like PPARg, adiponectin or fatty acids (Gillet et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes accumulation or lipid toxicity is frequently reported in various diseases, including postmenopausal osteoporosis, aging osteoporosis and osteonecrosis (Gillet et al, 2017). Some investigators found that bone marrow adipocytes could suppress osteoblast differentiation through secreting factors like PPARg, adiponectin or fatty acids (Gillet et al, 2017). Besides analyzing the bone tissue directly, biomarkers of bone turnover in serum or urine are frequently used to investigate the metabolic status of bone in both bench and clinical (Takahashi et al, 2010;Wheater et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that MSCs of patients with ON (ON MSCs) can proliferate and differentiate in the hypoxic area. Adipogenesis seems to be intensified in ON MSCs [ 22 ]. Cellular mechanisms of protection against lipotoxicity, such as stearyl-coenzyme A desaturase 1 and carnitine palmitoyl transferase 1 expression are dysregulated in ON MSC; moreover, palmitate-induced interleukin (IL)-6 and IL-8 secretion is higher in ON MSC [ 22 ].…”
Section: Pathogenesis Of Onmentioning
confidence: 99%